2018
DOI: 10.1155/2018/6959761
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an HPLC-MS/MS Method for Rapid Simultaneous Determination of Cefprozil Diastereomers in Human Plasma

Abstract: Background Both cis- and trans-cefprozil have antimicrobial activity, but their potencies are quite different. It is therefore necessary to develop a sensitive method to simultaneously determine both isomers for pharmacokinetic and bioequivalence studies. Methods An LC-MS/MS method, using stable isotope-labeled cefprozil as the internal standard, was developed and validated. The analytes were extracted from plasma by protein precipitation and separated on a reverse-phase C18 column using a gradient program con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
1
7
1
Order By: Relevance
“…The reported maximum blood concentration (C max ), time to reach C max (T max ) and area under the plasma concentration-time curve (AUC) of cis -cefprozil ranged from 12.3 to 17.3 μg/mL, 1.75 to 2.06 h, and 46.0 to 65.0 μg·h/mL, which is similar to our results of 15.0 μg/mL, 1.96 h, and 59.6 μg·h/mL. The half-life (t 1/2 ) of cis -isomer in this study was 1.67 h, which was not significantly different from the reported values (1.72-1.87 h) [13,24,32]. In case of trans -cefprozil, the reported C max , T max , AUC, and t 1/2 were 1.33–1.93 μg/mL, 2–2.13 h, 4.40–7.12 μg·h/mL, and 1.4–1.66 h, which were similar to our results (1.63 μg/mL, 1.96 h, 6.38 μg·h/mL, and 1.50 h) [13,32].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The reported maximum blood concentration (C max ), time to reach C max (T max ) and area under the plasma concentration-time curve (AUC) of cis -cefprozil ranged from 12.3 to 17.3 μg/mL, 1.75 to 2.06 h, and 46.0 to 65.0 μg·h/mL, which is similar to our results of 15.0 μg/mL, 1.96 h, and 59.6 μg·h/mL. The half-life (t 1/2 ) of cis -isomer in this study was 1.67 h, which was not significantly different from the reported values (1.72-1.87 h) [13,24,32]. In case of trans -cefprozil, the reported C max , T max , AUC, and t 1/2 were 1.33–1.93 μg/mL, 2–2.13 h, 4.40–7.12 μg·h/mL, and 1.4–1.66 h, which were similar to our results (1.63 μg/mL, 1.96 h, 6.38 μg·h/mL, and 1.50 h) [13,32].…”
Section: Discussionsupporting
confidence: 89%
“…The half-life (t 1/2 ) of cis -isomer in this study was 1.67 h, which was not significantly different from the reported values (1.72-1.87 h) [13,24,32]. In case of trans -cefprozil, the reported C max , T max , AUC, and t 1/2 were 1.33–1.93 μg/mL, 2–2.13 h, 4.40–7.12 μg·h/mL, and 1.4–1.66 h, which were similar to our results (1.63 μg/mL, 1.96 h, 6.38 μg·h/mL, and 1.50 h) [13,32]. In addition, PK parameters of total cefprozil (16.6 μg/mL for C max , 2.11 for T max , 66.0 μg·h/mL for AUC, and 1.66 h for t 1/2 ) in this study also did not differ significantly from the reported values for C max (18.3–18.8 μg/mL), T max (0.90–2.06 h), AUC (61.2–71.8 μg·h/mL), and t 1/2 (1.20–1.69 h) [11,19,32].…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Base peaks 208 and 158 were selected as a quantitative transition for CEF and CPH respectively, while m/z 184 was selected as a conformational transition for CEF. He et al (2018) utilized 391.2 as Q1 for CEF detection [12], this m/z is unreliable, where; the theoretical m/z for CEF in the adduct form [M+H] is 390.1 (389.1 monoisotopic mass plus 1.0 for hydrogen adduct), this theoretical m/z compiled with the observed m/z in our method and also with the recorded m/z within thereference spectrumfounded atmass bank of North America database. These unreliable transitions for CEF within He et al developed methodis uncommon in HPLC-MS/MS methods generation and hardly can be accepted.…”
Section: Chromatographic Conditions and Detection;mentioning
confidence: 99%
“…Method development for CEF diastereoisomers determination in the biological sample is a critical process due to the stereo-isomeric structure [5]. Several methodshave been reported for CEF determination in plasma samples [4,[6][7][8][9][10][11][12]_ ENREF_2_ENREF_2. The recent published paper by He et al (2018) show proper sensitivity and simplicity [12], however,itsuffer reliability which will be illustrated later.In this vein, a primary objective for this work was to introduce a simple, valid and reliablemethods for CEF diastereoisomers determination in human plasma.…”
Section: Introductionmentioning
confidence: 99%